ASPECTS OF KINETIC REHABILITATION IN INFRASPINATUS SYNDROME (GYMNASIUM, 2009)
Infraspinatus syndrome is defined as a condition of frequently painless atrophy of the infraspinatusmuscle caused by suprascapular neuropathy.We made a study of 20 subjects, average of age were 38 years, most of subjects were athlets andonly 3 subjects have not been athletes. The pain has an insidious onset and is described as a deep, dull,aching discomfort. Assesment methods included: physical assesment and functional assesment used specifictest for shoulder mobility and stability. Rehabilitation objectifes of this phase are: mentain shoulder mobility,prevention of muscltendinous retraction, promote scapular stabilization and shoulder stabilization, increasemotor and muscle control, coordinationHow we seen is important to make a good assesment for decide wich is the best way forrehabilitation and for return to play. So we consider that specific assesment can help us to observe thedynamic evolution in infraspinatus syndrome. Much more if we apply earlier the rehabilitation protocol thatwe propose is possible to reduce the risk of recidive and the risk to increase shoulder injuries.